Long-term effect of antiepileptic drug switch on serum lipids and C-reactive protein - Mintzer, Scott (Epilepsy Behav, 2016)
BACKGROUND: Prior studies have shown that switching patients from inducing antiepileptic drugs (AEDs) to lamotrigine, levetiracetam, or topiramate reduces serum lipids and C-reactive protein (CRP). These studies were all of short duration, and some drugs, such as zonisamide, have not been investigated. METHODS: We recruited 41 patients taking phenytoin or carbamazepine who were being switched to zonisamide, lamotrigine, or levetiracetam. We measured serum lipids and CRP before the switch, >6 weeks after, and >6 months after. An untreated control group (n=14) underwent similar measurement. We combined these data with those of our previous investigation (n=34 patients and 16 controls) of a very similar design. RESULTS: There were no differences in outcome measures between the two inducing AEDs, nor among the three non-inducing AEDs. Total cholesterol (TC), atherogenic lipids, and CRP were higher under inducer treatment than in controls. All measures were elevated under inducer treatment relative to non-inducer treatment, including TC (24 mg/dL higher, 95% CI: 17.5–29.9, p<0.001) and CRP (72% higher, 95% CI: 41–111%, p<0.001). The difference between drug treatments was clinically meaningful for atherogenic lipids (16%, 95% CI: 11–20%, p<0.001) but small for high-density-lipoprotein cholesterol (5%, 95% CI: 1–9%, p<0.05). All measures were stable between 6 weeks and 6 months after drug switch. CONCLUSIONS: We demontrate that switching from inducing to non-inducing AEDs produces an enduring reduction in serum lipids and CRP. These results provide further evidence that inducing AEDs may be associated with elevated vascular disease risk. These are the first vascular risk marker data in patients taking zonisamide, which shows a profile similar to that of other non-inducing AEDs.